Composition and Characteristics of Moduli for Automatic Analysis of Failures in Operation of Boiling and Turbine Equipment at Thermal Power Station - V. A. Yanitsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
The paper presents composition and brief characteristics of diagnostic moduli applied in an automatic system for detection and analysis of failures iii operation of boiling and turbine equipment at thermal power stations. Realization of automatic analysis in respect of technological situations makes it possible to form messages for duty personnel. These messages contain data which is considered as an important one at the actual moment and the messages have such form that ensures the most favourable conditions in order to take a decision pertaining to on-line control of the equipment operation.